BIG LABS AND TINY INSTRUMENTS - Blow, Nathan S Ph D (BioTechniques, 2017)
At many research institutions, lab space is more valuable than gold. Developers are taking note by designing smaller instruments with enhanced capabilities. Nathan Blow looks inside today's tiny lab